Immunometabolic alteration of CD4+ T cells in the pathogenesis of primary Sjögren’s syndrome - Chen, Yingying; Luo, Xuan; Deng, Chuiwen; Zhao, Lidan; Gao, Hui; Zhou, Jiaxin; Peng, Linyi; Yang, Huaxia; Li, Mengtao; Zhang, Wen; Zhao, Yan; Fei, Yunyun (Clinical and experimental medicine, 2024)
Primary Sjögren’s syndrome (pSS) is a prevalent autoimmune disorder wherein CD4 + T cells play a pivotal role in its pathogenesis. However, the underlying mechanisms driving the hyperactivity of CD4 + T cells in pSS remain poorly understood. This study aimed to investigate the potential role of immunometabolic alterations in driving the hyperactivity of CD4 + T cells in pSS. We employed Seahorse XF assay to evaluate the metabolic phenotype of CD4 + T cells, conducted flow cytometry to assess the effector function and differentiation of CD4 + T cells and measured the level of intracellular reactive oxygen species (ROS). Additionally, transcriptome sequencing, PCR, and Western blotting were utilized to examine the expression of glycolytic genes. Our investigation revealed that activated CD4 + T cells from pSS patients exhibited elevated aerobic glycolysis, rather than oxidative phosphorylation, resulting in excessive production of IFN-γ and IL-17A. Inhibition of glycolysis by 2-Deoxy-D-glucose reduced the expression of IFN-γ and IL-17A in activated CD4 + T cells and mitigated the differentiation of Th1 and Th17 cells. Furthermore, the expression of glycolytic genes, including CD3E, CD28, PIK3CA, AKT1, mTOR, MYC, LDHA, PFKL, PFKFB3, and PFKFB4 , was upregulated in activated CD4 + T cells from pSS patients. Specifically, the expression and activity of LDHA were enhanced, contributing to an increased level of intracellular ROS. Targeting LDHA with FX-11 or inhibiting ROS with N-acetyl-cysteine had a similar effect on reversing the dysfunction of activated CD4 + T cells from pSS patients. Our study unveils heightened aerobic glycolysis in activated CD4 + T cells from pSS patients, and inhibition of glycolysis or its metabolite normalizes the dysfunction of activated CD4 + T cells. These findings suggest that aerobic glycolysis may be a promising therapeutic target for the treatment of pSS.